Penguatan Strategi Sistem Nafkah Melalui Jejaring Sosial di Kalangan Migran Minangkabau Indonesia di Malaysia - Dhina Yuliana; Zulfan Saam; Indra Suandy; Rikki Afrizal (CANANG: Jurnal Pengabdian Masyarakat, 2026)
One of the traditions of the Minang people is to "migrate" both domestically and abroad, including in Malaysia. In general, the livelihood of Minang migrants is trading. The source of livelihood of various traders is maintained, some of these migrants have even become wealthy. However, there are also those who are able to survive as traders or fail and have to return home due to failure to trade in Malaysia. To provide empowerment to Minang migrants in Malaysia. The purpose of this training activity is to provide knowledge and motivation to become entrepreneurs for Minang migrants in Malaysia. The community service method is Focus Group Discussion (FGD) and Question Answer method. Training participants are administrators and traders of Padang Pariaman Saiyo in Selangor-Malaysia. Evaluation of the success of this research activity is by observing participant participation and the dynamics of the training process. The results of the community service research show that training participants can understand strategies for increasing trade (small and medium enterprises) through increasing entrepreneurial motivation and social networks, including through the activities of the Minang Saiyo Padang Pariaman social group in Malaysia.